A CPW‐fed quad‐directional stacked magneto‐dielectric resonator antenna for angle diversity application. Issue 1 (January 2016) - Mohit, Kumar; Gupta, Vibha Rani; Rout, S. K.
ABSTRACT: This article presents quad‐directional magneto‐dielectric (MD) resonator antenna configuration, designed using two different MD materials with stack configuration. These materials have been designed such that their temperature coefficient is approximately zero. The microwave dielectric constant (εr ) and permeability (μr ) of both materials are calculated by Nicholson–Ross–Weir conversion technique and found to be 8.02, 1.64 and 10.47, 1.52, respectively. The designed antenna can radiates in four directions simultaneously at the resonant frequency of 5.84 GHz. The beam shaping has been achieved using single feed and this property can be utilized for the angle diversity. © 2016 Wiley Periodicals, Inc. Microwave Opt Technol Lett 58:62–64, 2016